2003
DOI: 10.1021/ic026027w
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Transferrin and the Serum Ligands Citrate and Phosphate for the Binding of Aluminum

Abstract: A key issue regarding the speciation of Al(3+) in serum is how well the ligands citric acid and phosphate can compete with the iron transport protein serum transferrin for the aluminum. Previous studies have attempted to measure binding constants for each ligand separately, but experimental problems make it very difficult to obtain stability constants with the accuracy required to make a meaningful comparison between these ligands. In this study, effective binding constants for Al-citrate and Al-phosphate at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 79 publications
0
55
0
Order By: Relevance
“…Different speciation models [29][30][31][32][33][34][35][36] have been reported in the literature. As concerns the h.m.m.…”
Section: Absorbed Almentioning
confidence: 99%
See 2 more Smart Citations
“…Different speciation models [29][30][31][32][33][34][35][36] have been reported in the literature. As concerns the h.m.m.…”
Section: Absorbed Almentioning
confidence: 99%
“…Al III binders. [29][30][31][32][33][34][35][36] Daydé et al, 29 Jackson, 30 and Harris 31 have proposed inorganic phosphate as the main Al III binder, whereas Clevette and Orvig, 32 Duffield et al, 33 and Ö hman and Martin 34 have suggested that citrate (Cit) is the only important l.m.m. binder.…”
Section: Absorbed Almentioning
confidence: 99%
See 1 more Smart Citation
“…[134,136] In mM total Al(III) concentrations, which correspond better to aluminum overload conditions and those when the thermodynamic equilibrium is reached (monitored by multinuclear NMR; see later), the amount of phosphate-bound Al(III) increases significantly and ternary Al(III)-citrate-phosphate complexes can also be detected (see Table 6) [32].…”
Section: Serum Speciation By Al(iii) and Fe(iii) Ionsmentioning
confidence: 97%
“…Harris et al [134] used different UV spectroscopy, pH-potentiometry, and ESI-MS measurements to develop a model at an Al(III) concentration of ~10 µM, which is similar to the normal biologically relevant serum level (~0.1-0.3 µM) [135]. The speciation model provided in Table 6 of Ref.…”
Section: Serum Speciation By Al(iii) and Fe(iii) Ionsmentioning
confidence: 99%